Care in subsequent pregnancies following stillbirth: an international survey of parents. (30th November 2016) - Wojcieszek, AM; Boyle, FM; Belizán, JM; Cassidy, J; Cassidy, P; Erwich, JJHM; Farrales, L; Gross, MM; Heazell, AEP; Leisher, SH; Mills, T; Murphy, M; et al.
Abstract : Objective: To assess the frequency of additional care, and parents' perceptions of quality, respectful care, in pregnancies subsequent to stillbirth. Design: Multi‐language web‐based survey. Setting: International. Population: A total of 2716 parents, from 40 high‐ and middle‐income countries. Methods: Data were obtained from a broader survey of parents' experiences following stillbirth. Data were analysed using descriptive statistics and stratified by geographic region. Subgroup analyses explored variation in additional care by gestational age at index stillbirth. Main outcome measures: Frequency of additional care, and perceptions of quality, respectful care. Results: The majority (66%) of parents conceived their subsequent pregnancy within 1 year of stillbirth. Additional antenatal care visits and ultrasound scans were provided for 67% and 70% of all parents, respectively, although there was wide variation across geographic regions. Care addressing psychosocial needs was less frequently provided, such as additional visits to a bereavement counsellor (10%) and access to named care provider's phone number (27%). Compared with parents whose stillbirth occurred at ≤ 29 weeks of gestation, parents whose stillbirth occurred at ≥ 30 weeks of gestation were more likely to receive various forms of additional care, particularly the option for early delivery after 37 weeks. Around half (47–63%) of all parents felt that elements of quality, respectful care were consistently applied, such as spending enough time with parents and involving parents in decision‐making. Conclusions: Greater attention is required to providing thoughtful, empathic and collaborative care in all pregnancies following stillbirth. Specific education and training for health professionals is needed. Tweetable abstract: More support for providing quality care in pregnancies after stillbirth is needed. Plain Language Summary: Study rationale and design: More than two million babies are stillborn every year. Most parents will conceive again soon after having a stillborn baby. These parents are more likely to have another stillborn baby in the next pregnancy than parents who have not had a stillborn baby before. The next pregnancy after stillbirth is often an extremely anxious time for parents, as they worry about whether their baby will survive. In this study we asked 2716 parents from 40 countries about the care they received during their first pregnancy after stillbirth. Parents were recruited mainly through the International Stillbirth Alliance and completed on online survey that was available in six languages. Findings: Parents often had extra antenatal visits and extra ultrasound scans in the next pregnancy, but they rarely had extra emotional support. Also, many parents felt their care providers did not always listen to them and spend enough time with them, involve them in decisions, and take their concerns seriously. Parents were more likely to receive various forms of extra care in the next pregnancy if their baby had died later in pregnancy compared to earlier in pregnancy. Limitations: In this study we only have information from parents who were able and willing to complete an online survey. Most of the parents were involved in charity and support groups and most parents lived in developed countries. We do not know how well the findings relate to other parents. Finally, our study does not include parents who may have tried for another pregnancy but were not able to conceive. Potential impact: This study can help to improve care through the development of best practice guidelines for pregnancies following stillbirth. The results suggest that parents need better emotional support in these pregnancies, and more opportunities to participate actively in decisions about care. Extra support should be available no matter how far along in pregnancy the previous stillborn baby died. Tweetable abstract: More support for providing quality care in pregnancies after stillbirth is needed. This paper includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14424